Saccharomyces Boulardii Ameliorates Non-alcoholic Steatohepatitis in Mice Induced by a Methionine-Choline-Deficient Diet Through Gut-Liver Axis - Yang, An-Ming; Lin, Chien-Yu; Liu, Shih-Hao; Syu, Guan-Da; Sun, Hao-Jhe; Lee, Kuei-Chuan; Lin, Han-Chieh; Hou, Ming-Chih (Frontiers in Microbiology, 2022)
Non-alcoholic steatohepatitis (NASH) is affecting people worldwide. Changes in the intestinal microbiome are crucial to NASH. A previous study showed eradicating intestinal fungi ameliorates alcohol-induced steatohepatitis; However, the role of intestinal fungi in non-alcoholic steatohepatitis is unclear. Saccharomyces Boulardii (SB), a dietary supplement yeast, has been reported to restore the integrity of intestine. Here, we tested the effect of SB in the treatment of NASH. Eight-week-old C57/BL6 male mice were fed either a Methionine-Choline deficient (MCD) diet or normal chow diet (NCD) for 8 weeks. Half of the MCD diet-fed mice were gavaged with SB (5 mg/day), once daily. The remainder and NCD-fed mice were gavaged with normal saline as a control. MCD diet-fed mice on SB supplement showed better liver function, less hepatic steatosis and decreased inflammation. Both hepatic inflammatory gene expression and fibrogenic gene expression were suppressed in mice with SB gavage. Intestinal damage caused by MCD diet was tampered, the inflammation of intestine was decreased, and gut permeability was improved in mice given SB supplement. Deep sequencing of fecal microbiome showed increased level of potentially beneficial gut microbiota and increased microbiota diversity in SB-supplemented mice. SB supplement maintains gut integrity, increases microbial diversity and increases levels of potentially-beneficial gut microbiota. Thus, SB supplement attenuates gut leakage and exerts a protective effect against NASH. Our results provide a new insight for the prevention of NASH.